Rich information service delivery to mobile users using smart posters - Ayu, Media Anugerah; Mantoro, Teddy; Ismail, Siti Aisyah; Zulkifli, Nurul Syafiqah (2012)
Since 2005, when it was introduced to the markets, Near Field Communication (NFC) technology has been used in various applications with the aim to increase convenience in people's everyday life activities. This technology supports the concept of Ambient Intelligence to interact seamlessly with the computer using everyday objects to deliver information to the users. Users will not need to concentrate on how to use the computer, but they can focus on the main task that they want to do with the help of the invisible computers which is somehow hidden inside the artifacts. NFC embedded artifacts have enabled this concept into reality. This paper discusses its use in smart posters to deliver rich information to the users in a pleasant, convenient, and easy way.